Spatial responses of ecosystem water-use efficiency to hydrothermal and vegetative gradients in alpine grassland ecosystem in drylands. (August 2022) - Liu, Xiaoyi; Liu, Chao; Fan, Bihang; Li, Longguo; Tan, Bo; Jin, Zhongwu; Lu, Heng; Liu, Tiegang
Graphical abstract: Highlights: The spatial variations of water use efficiency were mainly controlled by gross primary productivity in the source region of the Yellow River. The water use efficiency showed significantly increasing trends along hydrothermal and vegetative gradients. A threshold of temperature was found in the spatial responses of water use efficiency to thermal gradients. The responses of water use efficiency to vegetative gradients reflected the indirect effects of hydrothermal conditions. Abstract: The carbon–water cycle is critical to ecosystem function and sustainability in dryland region. Ecosystem water use efficiency (WUE) is an important indicator reflecting the interaction between carbon and water, and investigating its spatial responses to hydrothermal and vegetative gradients is vital to understand the underlying mechanism of carbon–water coupling. The source region of the Yellow River (SRYR) is a typical alpine grassland ecosystem in drylands characterized by cold and arid climate, which is ecologically fragile and sensitive to environmental factors. In this study, we investigated the spatial variations of ecosystem WUE in the SRYR during 2000–2014 and examined its underlying drivers. The mean annual WUE showed significantly increasing trends along hydrothermal and vegetative gradients from semi-arid zone (SA) to dry sub-humid zone (DSH), with the average value of 0.59 ± 0.35 gC kg −1 H2 O. The spatial variations of WUE were mainly controlled by gross primary productivity (GPP) rather than evapotranspiration (ET). Compared to precipitation (P), temperature (Ta ) better explained the spatial variations of WUE. And a temperature threshold of 0 °C was found, which indicated a shift of sensitivity of WUE to thermal conditions from permafrost to seasonally frozen ground due to the effects of low temperature on photosynthetic process in alpine grassland ecosystem. The responses of WUE to LAI gradients reflected the indirect effects of hydrothermal conditions on WUE by altering LAI. This study improves our understanding of the spatial responses of the regional carbon and water interactions to environmental conditions.